Social plasticity in choosiness in green tree frogs, Hyla cinerea. (22nd August 2017) - Neelon, Daniel P; Höbel, Gerlinde
Abstract : Female frogs travel long distances in pursuit of the best male, but will not waste time searching for Mr. Perfect if they know he is not around. Using audio playbacks, we find that females were less choosy when no attractive males were heard, helping them to avoid wasting energy searching for a male who is not there. However, introducing a new male of a different species also makes females less choosy, which can have negative consequences for reproduction. Abstract: Mate choice is an important driver of the evolution of sexual traits and can promote divergence and speciation. Understanding the underlying variation in mate choice decisions is crucial to understand variation in the strength and direction of sexual selection. We explored whether variation in the social environment influences mate choice decisions and focus on the aspect of mate choice termed choosiness (i.e. the effort invested in mate assessment and acquisition). Using call playbacks, we manipulated the social environment female green tree frogs would experience as they entered a chorus, and then we conducted two-choice playback trials to assess whether females exhibited social plasticity in choosiness. We explored social plasticity at 2 levels: in one experiment, we manipulated the presence or absence of preferred (attractive) and less preferred (unattractive) conspecific males (i.e. intraspecific context), and in the other experiment, we manipulated the presence or absence of preferred (conspecific) and less preferred closely related heterospecific males (i.e. interspecific context). We found that in the intraspecific context, the presence of attractive males increased choosiness, while absence of attractive males reduced choosiness. In the interspecific context, choosiness remained stable in most treatments, but was lowered when females experienced a mixture of conspecific and heterospecific calls. We discuss the effect of social plasticity in choosiness on mate choice decisions and highlight its evolutionary consequences.